Psychopathy, criminal intentions, and abnormal appraisal of the expected outcomes of theft - Próspero-Luis, João (Legal and criminological psychology, 2017)
Purpose. Impaired emotional learning is one of the hallmark features of psychopathy. The abnormal processing of cues of reward and punishment, and its impact in decision-making, has mostly been supported by laboratorial studies. In this report, we have analysed the effect of psychopathy in the formation of attitudes towards committing theft, and its impact in the intention to reoffend after release. Methods. A self-report instrument to characterize the predictors of the intention to reoffend was developed and administrated, along with the Triarchic Psychopathy Measure, to a sample of 91 male inmates convicted for theft. Results. The perceived rewards of theft mediated the association between psychopathic traits and the intention to reoffend. The analysis of the expectancy and value components of the attitude towards theft showed that psychopathic traits are associated with reduced expectancy of negative outcomes and increased expectancy of positive outcomes as a consequence of reoffending. Conclusions. Our results add support to the role of disrupted expectancy–value learning and increased reward sensitivity as mediators of the increased probability to reoffend in psychopathy.